Rodent-borne diseases in Thailand: targeting rodent carriers and risky habitats - Vincent Herbreteau; Frédéric Bordes; Sathaporn Jittapalapong; Yupin Supputamongkol; Serge Morand (Infection Ecology & Epidemiology, 2012)
Background: Comparative analysis, which aims at investigating ecological and evolutionary patterns among species, may help at targeting reservoirs of zoonotic diseases particularly in countries presenting high biodiversity. Here, we developed a simple method to target rodent reservoirs using published studies screening microparasite infections. Methods: We compiled surveys of microparasites investigated in rodents trapped in Thailand. The data comprise a total of 17,358 rodents from 18 species that have been investigated for a total of 10 microparasites (viruses, bacteria and protozoans). We used residual variation of microparasite richness controlled for both rodent sample size and pathogens’ screening effort to identify major rodent reservoirs and potential risky habitats. Results: Microparasite species richness was positively related to rodent sample size and pathogens’ screening effort. The investigation of the residual variations of microparasite species richness showed that several rodent species harboured more pathogens than expected by the regression model. Similarly, higher pathogen richness than expected was observed in rodents living in non-flooded lands, forests and paddy fields. Conclusion: Our results suggest to target some rodent species that are not commonly investigated for pathogen screening or surveillance such as R. adamanensis or B. savilei, and that non-flooded lands and forests should be more taken into caution, whereas much surveys focused on paddy rice fields and households.